Nutri-case blueprint / Muhammad Nabil Jumain...[et al.] - Jumain, Muhammad Nabil; Shuhaimi, Nur Adiina Iffah; Sabtu, Nur Syafawani; Ahmad Shapiki, Riqqatunnafsi; Arman, Sulaiman (2018)
Nutri-Case is a multifunctional food container with special features being developed to enhance the usage of a normal and basic food container. The idea behind this special food container is for workers and students who practice a healthy lifestyle to be able to enjoy their healthy and homemade meals while they are still warm during their breaks or lunch time. Nutri- Case enables the users to heat their food, without the use of microwave or gas stove, which could be a hassle and time consuming, by using the heat plate installed in the food container itself. This special food container also comes with an LCD interactive display cover which the users are able to receive the nutritional information regarding the meal that they have prepared. Nutri-Case is also developed to encourage workers and students who might be too busy to practice a healthy lifestyle by preparing their own meals.